2021
DOI: 10.1186/s12913-021-06440-1
|View full text |Cite
|
Sign up to set email alerts
|

Use and usability of the dr. Bart app and its relation with health care utilisation and clinical outcomes in people with knee and/or hip osteoarthritis

Abstract: Background Self-management is of paramount importance in the non-surgical treatment of knee/hip osteoarthritis (OA). Modern technologies offer the possibility of 24/7 self-management support. We developed an e-self-management application (dr. Bart app) for people with knee/hip OA. The aim of this study was to document the use and usability of the dr. Bart app and its relation with health care utilisation and clinical outcomes in people with knee/hip OA. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…The 15 included articles were published between 2015 and 2023. Countries of origin of these studies were: United States (n=3) [ 25 , 26 , 36 ], Australia (n=2) [ 32 , 38 ], South Korea (n=2) [ 29 , 35 ], the Netherlands (n=1) [ 31 ], Italy (n=1) [ 27 ], Belgium and Italy (n=1) [ 30 ], Thailand (n=1) [ 37 ], and Taiwan (n=1) [ 33 ]. A total of 3 publications did not specify in which country the study was performed [ 28 , 34 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The 15 included articles were published between 2015 and 2023. Countries of origin of these studies were: United States (n=3) [ 25 , 26 , 36 ], Australia (n=2) [ 32 , 38 ], South Korea (n=2) [ 29 , 35 ], the Netherlands (n=1) [ 31 ], Italy (n=1) [ 27 ], Belgium and Italy (n=1) [ 30 ], Thailand (n=1) [ 37 ], and Taiwan (n=1) [ 33 ]. A total of 3 publications did not specify in which country the study was performed [ 28 , 34 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the study design, 8 publications followed a quasi-experimental approach [ 26 - 29 , 32 , 35 , 38 , 39 ], 5 were randomized controlled trials [ 25 , 30 , 33 , 36 , 37 ], and 2 were exploratory studies [ 31 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although participants and interventions were not the same, other similar studies on mHealth have reported no significant differences in QoL outcomes between mHealth and control groups [ 12 , 30 ]. A systematic review with a specific PICO model should be used to determine the effectiveness of mHealth on QoL.…”
Section: Discussionmentioning
confidence: 99%
“…For example, our search did not yield "Dr. Bart," a Dutch app for people with knee and/or hip OA that has been studied in the Netherlands and Germany. 42,43 Future joint international efforts in identifying and appraising apps targeting the management of knee and/or hip OA would enhance global generalizability. In addition, we used a threshold score of ≥3/5 as a minimum acceptable total MARS score for inclusion in the final app summary.…”
Section: Strengths and Limitationsmentioning
confidence: 99%